THE INFLUENCE OF GREEN INNOVATION, LIQUIDITY, AND INTEGRATED REPORTING ON THE VALUE OF FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2023 - Alifiannisa, Marshanda (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This research from to determine the influence of green innovation, liquidity, and integrated reporting on the value of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. This research uses a quantitative approach, with a population of 92 food and beverage sub-sector companies that are still listed on the Indonesia Stock Exchange from 2019 to 2023, and the sample in this research is 19 companies where the sampling technique uses purposive sampling. The analysis technique used is panel data regression analysis with the help of the Eviews 12 program. The results of this research show that partially green innovation has no effect on the value of the company, the liquidity variable has a positive effect on company value, and the integrated reporting variable has a negative effect on company value.